Investigating the role of extension officers in supporting social learning of rainwater harvesting practices amongst rural smallholder farmers in Nkonkobe Local Municipality, Eastern Cape - Sithole, Phindile Nomfundo (Rhodes University, Faculty of Education, Department of Environmental Learning Research Centre, 2019)
Water is essential for food production, however South Africa's water is already under pressure due to increasing population, food demand, and climate change, amongst other factors. Over the past years, there has been increasing demand for agricultural water use for food production due to these factors. Rainwater harvesting and conservation (RWH&C) for food production is one of the most promising approaches to address increasing demand of water. The Rhodes University Environmental Learning Research Centre have led a project with the Water Research Commission (Project No. K5/2277) focusing on the dissemination of RWH&C practice knowledge that involves some of the extension services in the Nkonkobe Municipality in the Eastern Cape, called the 'Amanzi [Water] for Food' project. While extension services were included in the project, the wider role of extension services in 'disseminating' RWH&C knowledge amongst farmers is not clear, a problem which provides the focus for this research, especially since there are changes in the designated role of extension services to become more responsive and reflexive in relation to farmers emerging needs, and in response to wider issues such as climate change and water scarcity. In general, there is agreement that the role of extension is to be active within the farming community, to facilitate social interactions and collaborative processes that often focus on activities that are intended to find, assess, interpret and adapt information, knowledge and evidence that are suitable for farmer's needs. Extension should also be available to identify arising issues that the farmers experience that can be solved by the use of research knowledge. However, little is known with regard to whether extension officers are taking up this role effectively, especially in relation to RWH&C knowledge. Using document analysis, semi-structured interviews, field-based observations and focus group discussions, this research seeks to demonstrate the role of extension services in facilitating and supporting social learning of RWH&C practices amongst rural smallholder farmers for improved food security. It provides insight into the way in which extension officers are able to facilitate social learning using RWH&C knowledge, and the issues that affect the adoption of social learning approaches to extension support related to RWH&C knowledge uptake and dissemination.
Keywords: Water harvesting -- South Africa -- Eastern Cape; Rainwater -- South Africa -- Eastern Cape; Water-supply, Agricultural -- South Africa -- Eastern Cape; Water-supply, Rural -- South Africa -- Eastern Cape; Agricultural extension workers -- South Africa -- Eastern Cape